The Effect of Spiritual Leadership on Ccontextual Performance: An Analytical Study At the University of El-TARF - Zouiti, Sarra (Journal of Human Sciences, 2022)
The study aimed to analyze and measure the influence of spiritual leadership & its dimensions on the level of contextual performance of faculty members at the Universityof El-Tarf / Algeria from their point of view.To achieve the goal, a questionnaire was developed to collect data, & it was distributed to a random sample of (75) permanent faculty members at the researched university.The results showed a high agreement on the level of applying the dimensions of spiritual leadership (vision, hope/faith, & altruism) in the researched university, with a percentage of (81.3%).The results also showed the existence of a statistically significant correlation and influence relationship at (α≤0.05) between the level of application of spiritual leadership and the level of contextual performance of faculty members.In light of these results, it was recommended to strengthen the role of spiritual leadership in order to achieve improvement in the level of contextual performance of the faculty member in the researched university.